Análise da sobrevivência, locomoção e ultraestrutura muscular e mitocondrial de Drosophila melanogaster com parkinsonismo induzido por paraquat - Neves, Paula Fernanda Ribas (2020)
In humans, Parkinson's disease (PD) is a neurodegenerative process that can occur sporadically, familial or associated with environmental factors, as pesticides exposure like Paraquat (PQ). Fruit fly, Drosophila melanogaster, has been widely used as a biological model for study of familial PD, involving mutants for genes overexpression or null genes, as well as studies of parkinsonism produced by inducing agents, as PQ. Although there are many studies on neuronal effects of PQ in D. melanogaster, there is scarce research on the effects of PQ on the muscular and mitochondrial ultrastructure of D. melanogaster, neither its effects on survival and locomotion parameters, at different ages, in this same biological model. Thus, the goal of present study was to evaluate survival, locomotion and ultrastructural parameters of mitochondrial and muscular fibers, using a 48 hour survival curve; open field test, evaluated by Anymaze software; and transmission electron microscopy (MET) associated to planar morphometry and stereology techniques, in 2 and 15-days-old D. melanogaster, treated with different PQ doses (0 - control, 10, 50, 100, 150 and 200mM), diluted in medium. We observed that PQ has a higher lethality in 15-days-old flies, with 20% mortality in PQ10mM, 60% in PQ50mM and 100% in doses above PQ100mM. In 2-days-old flies, a 20% mortality can be observed, only at PQ150mM dose, and PQ200mM presents as a lethal dose, in both groups. Regarding locomotion, in 15-days-old animals, PQ10mM and PQ50mM doses induce a significant reduction in the following locomotor parameters: distance travelled, average speed and average speed in mobile time (p <0.05), indicating parkinsonian signs of bradykinesia (slow movements). The 2-days-old animals showed no differences in any of the locomotor parameters analyzed, in any PQ doses, when compared to controls. Reductions in survival and locomotion probably induced by acute treatment with PQ are not associated with ultrastructural changes in mitochondrial and muscular, since in all parameters evaluated in MET images (density, percentage of area covered, area and shape coefficient “Shape Z ”), no differences were found regarding to controls, in both doses and ages evaluated (Control and PQ50mM; 2 and 15-days-old). Thus, this study demonstrates that treatment with PQ is more harmful, at least concerning survival and locomotion, in mature individuals (15-days-old) when compared to young individuals (2-days-old). Furthermore, PQ acute treatment did not cause ultrastructural differences in muscle fibers and mitochondria, as previously described in the literature in D. melanogaster mutants with familial PD, as PINK1 and parkin.